Exosomes Secreted by Adipose-Derived Mesenchymal Stem Cells Foster Metastasis and Osteosarcoma Proliferation by Increasing COLGALT2 Expression - Wang, Yan; Chu, Yijing; Li, Kun; Zhang, Guoqing; Guo, Zhu; Wu, Xiaolin; Qiu, Chensheng; Li, Yan; Wan, Xin; Sui, Jing; Zhang, Dan; Xiang, Hongfei; et al. (Frontiers in Cell and Developmental Biology, 2020)
Objectives: Homosapien collagen β (1-O) galactosyl transferase 2 (COLGALT2) is an important enzyme during collagen glycosylation, yet its biological functions in cancer are incompletely understood. Our previous study revealed that in the osteosarcoma microenvironment, adipose-derived mesenchymal stem cells (ADSCs) have cancer-promoting effects, but the exact mechanisms remain unclear. The aim of this study was to investigate the role of COLGALT2 in the osteosarcoma-fostering effects of ADSCs. Materials and Methods: In this study, we compared COLGALT2 expression between primary and metastatic osteosarcoma tissues and found that metastatic tissues expressed significantly higher COLGALT2 levels. Then, we isolated and identified exosomes secreted by ADSCs. We also evaluated the roles of ADSC exosomes and COLGALT2 in the osteosarcoma-promoting effects of ADSCs. Results: Our results showed that ADSC exosomes could foster the invasion, migration and proliferation of osteosarcoma cells, together with increased COLGALT2 expression. COLGALT2 inhibition in MG63 cells suppressed the ADSC exosome-mediated fostering of osteosarcoma cell invasion, migration and proliferation in vitro. Conversely, COLGALT2 overexpression promoted U-2OS cell invasion, migration and proliferation in vitro. Moreover, COLGALT2 inhibition attenuated metastasis and tumour growth, and ADSC exosomes promoted tumour progression, as demonstrated in a nude mouse model of osteosarcoma. Conclusions: Based on these data, ADSC exosomes foster osteosarcoma progression by raising COLGALT2 expression in osteosarcoma cells.